2007
DOI: 10.1159/000127420
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Paclitaxel/Carboplatin Radiochemotherapy for Stage III/IV Resectable Oral and Oropharyngeal Cancer: Seven-Year Follow-Up of a Phase II Trial

Abstract: Numerous treatment concepts for advanced but resectable oral and oropharyngeal squamous cell carcinoma exist. In this study, we present the 7-year results of a promising treatment with preoperative simultaneous chemoradiation using paclitaxel and carboplatin within a prospective phase II trial comprising 56 patients. After determination of the local tumor extension, chemoradiation was applied for 4 weeks and up to 40 Gy. Following a recovery period of 3–4 weeks, tumor resection was performed within the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…A major problem in analyzing staging data of head and neck carcinoma is that, today, locally advanced carcinoma is often treated with non‐surgical organ preservation strategies as first line of management. Combining these strategies offers the opportunity of tissue preservation and retained functional integrity 35–37. As a result, surgical data to obtain a pTNM are often not available.…”
Section: Discussionmentioning
confidence: 99%
“…A major problem in analyzing staging data of head and neck carcinoma is that, today, locally advanced carcinoma is often treated with non‐surgical organ preservation strategies as first line of management. Combining these strategies offers the opportunity of tissue preservation and retained functional integrity 35–37. As a result, surgical data to obtain a pTNM are often not available.…”
Section: Discussionmentioning
confidence: 99%
“…Klug et al reported of complete histological response in 48.3% for a combined mitomycin, 5-fluorouracil (5-FU) and radiation therapy (50 Gy) [24], and Eckardt et al could observe a complete response in even 58% of their patients treated by neoadjuvant radiotherapy (40 Gy) plus carboplatin and taxane [9]. In the latter, prospective, nonrandomized phase II trial on 56 patients, an overall survival of 84% after 3 years was described, dropping to 63.3% after 7 years, while recurrence-free survival still was 84.5%, indicating stable local tumor control [9,10]. These results with additional taxane promise a possible benefit in comparison to the own concept with respect to histological tumor response and long-term outcome, as the 5-year survival of 76.2% in our study describes DSS and cases without residual tumor after surgery.…”
Section: Authorsmentioning
confidence: 99%
“…In addition, the inclusion criteria that define high-risk tumors vary between the different studies [6]. Several studies have examined the effects of neoadjuvant RCT followed by radical surgery on OSCC [19,22,26,33,39]. To the best of our knowledge, there is only one study that compared the results of adjuvant RT and RCT in advanced tongue carcinoma but no study that focuses on the effects adjuvant RCT in patients with squamous cell carcinoma from all sites of the oral cavity excluding tumors from other sites of the head and neck region [24].…”
Section: Introductionmentioning
confidence: 99%